Impacts of landscape spatial configuration of integrated multi-pond constructed wetlands in a basin on the treatment of non-point source pollution. (10th January 2023) - Li, Dan; Chu, Zhaosheng; Li, Pushuang; Xu, Wenyi; Wang, Enrui; Jin, Chunling; Zheng, Binghui
Abstract: To assess the retention performance of integrated multi-pond constructed wetlands (MPCWs) for the interception of non-point source (NPS) pollution in a basin, the examination of catchment divisions was applied to explore the impacts of the landscape spatial configuration of MPCWs on the treatment of NPS pollution. An empirical assessment model was established to determine the characteristics of the nitrogen and phosphorus removal performance of MPCWs in different catchment divisions. Average interception efficiencies of TN (4.18%) and TP (5.05%) in the catchment divisions were achieved. The scattered distribution of MPCWs in an annular shape in the catchment was helpful for the collection and interception of wastewater, while the spatial configuration of several MPCWs positioned in a straight line along the elevation obtained unsatisfactory interception performance. The result of the relationship between spatial configuration parameters and interception performance of MPCWs in the catchments estimated that choosing reasonable site locations, increasing the ratio of the MPCW area to the catchment area (A: Ac ), the number, areas, and volume of MPCWs in the catchment, and optimizing other spatial configuration parameters such as following the flow direction, connecting to the river or ditch systems, all contributed to the interception performance of MPCWs for the NPS pollution. The overall planning perspective on local special land resources, pollution source structure, and the sustainable allocation of rural agricultural water resources for the parameters optimization of geographical landscape structure was highlighted in the scientific management of MPCWs for controlling NPS pollution in a basin. Graphical abstract: Image 1 Highlights: The established empirical model can well estimate the pollutant removal performance. Spatial configuration parameters affected the interception performance of MPCWs. Multi-inlets of MPCWs positioned in an annulus shape aided wastewaters collection. MPCWs connected to the river or ditch system obtained good interception efficiencies. Optimizing geographical parameters of MPCWs promoted the control of NPS pollution.